(untitled) (TAJ: Journal of Teachers Association, 2009)
The incidence of gastric cancer has declined from half a century ago in the west. However, contrary to general trend of steady decline in the incidence of gastric cancer, many western countries have noticed in recent decades an increase in gastric cancer in cardia with declining trend in distal involvement. In the developed world including the Japan, the highest prevalent country of gastric cancer, the distal stomach has remained predominant although a trend toward a proximal shift has been noted. So the study was performed to estimate the cancer by tumour location in Bangladesh. One hundred and sixty five patient were endoscopically assessed for location of cancer. The age range of the patients were 19 to 70 years and male outnumbered the female (2:1). The stomach is divided apparently into upper, middle and lower third by dividing the lesser and greater curvature in two equidistant points and joining the points. Distal or antral gastric carcinoma was found to be the commonest location (56.9%) followed by body (29.6%), cardia (9.09%) and diffusely involved (4.2%). The study also depicted no significant change in location of tumour with age of the patients. All patients were subjected to serological test for H. pylori and 106(64.2%) gave positive results. In conclusion, Bangladeshi population has shown no change in age predilection with site specificities of gastric carcinoma and the antrum continues to be the commonest site of malignancy. doi: 10.3329/taj.v20i2.3067 TAJ 2007; 20(2): 95-98